The Effectiveness of Influencer Endorsements on Online Fashion Sales Levels - Namira Ummi Khalsum. YB (Smart International Management Journal, 2024)
Given importance of marketing strategies in the digital era, this study investigates the effect of influencer endorsements on online fashion product sales. A quantitative experimental design was employed involving 100 respondents, who were divided into experimental and control groups. The results show that influencer endorsement increased product sales by 108.33% and raised consumers’ purchase intention from an average score of 3.2 to 4.5 after exposure to endorsement content. Statistical analysis using the Mann–Whitney U test revealed a significant difference between the two groups (U = 450, p = 0.002). These findings indicate that influencer endorsement is an effective marketing strategy for promoting fashion products online. The study highlights the importance of selecting credible and relevant influencers aligned with the target market. Nevertheless, this research is limited by respondent demographics and the range of social media platforms examined; therefore, further studies are recommended to include broader samples and additional influencing factors.